Pencegahan Stunting melalui Intervensi Terintegrasi Gizi, Sanitasi Lingkungan, dan Pemberdayaan Masyarakat di Desa Kemloko Temanggung - Three Haryanto, Anggit; Izzati, Fifi Sufaira; Effendi, Rosiana Luthfia; Aufa, Muhammad Rifqi; Hanina, Fildanum Syalwa; Fadhilatil Hidayah, Salma Nur; Lituhayu, Kirana Dewangkari Kingkin; Wulandari, Qeis; Widodo, Cahyo; Salsabila, ‘Ainu Hanum; Paska, Yesica Apriliana (Gotong Royong, 2026)
Stunting is a public health problem related to nutritional status, environmental sanitation, and clean and healthy living behaviors. In Kemloko Village, the problem is exacerbated by the limited use of local food ingredients and poor household waste management. This community service activity aims to support stunting prevention efforts in Kemloko Village through an integrated approach based on improving nutrition and environmental improvement. The method used in this study is Participatory Action Research (PAR), which actively involves the community in the process of problem identification, planning, implementation, and evaluation of the program. The program implemented includes waste management education, the establishment of a waste bank, the provision of locally sourced food-based PMT (Food Supplements), and a workshop on the use of used cooking oil. The results of this activity indicate an increase in community understanding of environmental hygiene and health, positive acceptance of locally sourced food-based PMT for toddlers, and an increase in the skills of PKK mothers in household waste management. Overall, the results of this study indicate that an integrated approach through community participation has the potential to support stunting prevention and improve the community's quality of life in a sustainable manner.